Determinan Pertumbuhan Ekonomi Regional di Provinsi Maluku, 2005-2010 - Yerimias Manuhutu (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2011)
Main purpose of this research is to evaluate and test variables that influencing regional economic growth in Maluku Province year 2004-2009 by using dynamic panel data method. Factors that influencing regional economic growth in Province of Maluku are private investment; government investment; infrastructure and labor. Result of this research indicating that panel of co-integration test with approach of parametric of group rho-statistic is 4,79 while group pp-statistic has a coefficient co-integration -12.18 whereas coefficient of co-integration by using group adf-statistic is -3.19. Probability of each examination indicating that variable with application of co-integration significant at level 1 percent only panel v-statistic at level 5 percents from seven panel model, got result that any variable of research co-integrated, in short term and long term has a positive direction to regional economic growth, meaning that if the independent variables increasing dependent variable will follow in same direction of movement. Keywords: regional economic growth, investment, panel dynamics